Chikungunya: a decade of burden in the Americas - William M. de Souza; Guilherme S. Ribeiro; Shirlene T.S. de Lima; Ronaldo de Jesus; Filipe R.R. Moreira; Charles Whittaker; Maria Anice M. Sallum; Christine V.F. Carrington; Ester C. Sabino; Uriel Kitron; Nuno R. Faria; Scott C. Weaver (Elsevier, 2024)
Summary: In the Americas, one decade following its emergence in 2013, chikungunya virus (CHIKV) continues to spread and cause epidemics across the region. To date, 3.7 million suspected and laboratory-confirmed chikungunya cases have been reported in 50 countries or territories in the Americas. Here, we outline the current status and epidemiological aspects of chikungunya in the Americas and discuss prospects for future research and public health strategies to combat CHIKV in the region.